Blake Cahill: capstone - Cahill, Blake, artist (Colorado State University. Libraries, 2024)
The artist's statement: I'm a passionate visual artist with a strong dedication to bringing conceptual material to reality. I was born near Denver, Colorado and now attend Colorado State University, pursuing a Bachelor of Fine Arts (BFA) with concentrations in Electronic Art and Graphic Design. I have always had a strong interest in the arts with a developed focus on communicating ideas through primarily digital mediums. My work often portrays a unique blend between the human experience and the shift toward a digital future. I maintain an audience focused structure, often utilizing an interactive approach, in my work that allows for an effective communication of ideas in a visually captivating way.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: electronic art